Evaluation of ozonated and ultrasonically treated corn starch as an adsorbent for patulin in buffer solutions - Tarek A. El-desouky (Scientific Reports)
Abstract This study evaluates the potential of ozonated corn starch (OCS) and ultrasonicated ozonated corn starch (USOCS) as adsorbents for patulin removal in buffer solutions. The results indicated that dual modification significantly altered the starch’s structure, introducing functional groups such as carbonyl and carboxyl groups, and increasing its surface area. These modifications led to enhanced patulin adsorption capacity. Adsorption efficiency was tested across different adsorbent doses (150 mg, 200 mg, 250 mg) and contact times (15, 30, 45, and 60 min). The highest removal efficiency of 92.5% was recorded for the 250 mg dose at 60 min, with USOCS showing superior performance compared to native corn starch and OCS. Kinetic studies revealed that the pseudo-second-order model provided the best fit for the adsorption process, indicating chemisorption as the dominant mechanism. The Langmuir and Freundlich isotherms were used to describe the adsorption behavior, with a maximum adsorption capacity (q max ) of 15.19 µg/mg and a Langmuir constant (K L ) of 54.00 L/µg for the 250 mg dose. Additionally, the modified starch demonstrated consistent adsorption performance at varying concentrations, with a favorable adsorption intensity (n > 1), supporting its potential for practical applications. These findings highlight the modified corn starch as an efficient, biodegradable, and low-cost adsorbent suitable for mitigating patulin contamination in food products, offering a sustainable alternative for improving food safety.